Danger and other unknown risks - North, Ryan, 1980-; Henderson, Erica (Penguin Workshop, an imprint of Penguin Random House LLC, 2023)
Here's the deal--on midnight of January 1st, 2000, the world ended. But it wasn't technology that killed it: it was magic. Now, years later, the Earth has transformed. Magic works (sort of). People are happy (sort of). But this new world isn't stable, and unless Marguerite de Pruitt and her canine pal, Daisy, do something about it, it'll tilt into deadly chaos. Good thing they've been training their whole lives for this, and are destined to succeed. Or so they think. A story about the search for truth, chosen family, and rebirth, the journey of Marguerite and Daisy seeks to ask one vital question: How far are you willing to go to save the world? --